PERSEPSI PELAYANAN TERHADAP PARTISIPASI ANGGOTA KUD LEMBAH SAWIT DI DESA SIALANG BARU KECAMATAN LUBUK DALAM KABUPATEN SIAK - Renavika '; Rosnita '; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The study aims to: 1) analyze perception service and level of participation of member KUD Lembah Sawit. 2) knowwhere the service perceptions that influence the participation of members of KUD Lembah Sawit. This study as conducted with survey and sampling methods using simple random sampling as many as 48 samples. Analysis of data using the Likert Scale’s Summated Rating (SLR) and multiple linear regression with the help of SPSS version 16. Result illustrate that perceptions of service KUD Lembah Sawit in middle category with a score of 2.10 and the level of participation of members of KUD Lembah Sawit in middle category with score 1,99. The amount of influence perceptions of members of 63,7% as seen from the adjusted R square value, which means that the influence of a strong cooperative service given to the participation of members of KUD Lembah Sawit. Perceptions service cooperative that affect the participation of members of KUD Lembah Sawit are service saving and loan and service waserda. Saving and loan service affect the level of participation of members indicated very significant (0,00<0,05) whereas ditunjukkan waserda service with a significant level (0,02<0,05).   Keywords: Perception of service, participation of member, likert’s scale